CORRELATIONAL AND EVOLUTIVE ANALYSIS OF HEAVY METALS IN STREAM SEDIMENTS FROM SANTA RIVER BETWEEN HUARAZ-CARHUAZ, DEPARMENT OF ANCASH-PERU - Rivera Mantilla, Hugo (2008)
The current geochemistry-statistical study of fourteen heavy metals on stream sediments in a sector of Rio Santa basin, showed that metals which have a normal distribution are Cr-Cu-Mo-Pb-V and metals with lognormal distribution are As-Cd-Fe-Hg-Ni-Sb- Sn-W-Zn. The abundance average demonstrated that the Zn is the most abundant metal and the Hg appears in small amounts. In the Batholith of the Cordillera Blanca predominates As-Sb-W, in the Volcanic Calipuy Cd-Cr-Cu-Hg-Mo-V and in the Group Goyllarisquizga Ni-Pb-Zn. According to the evolution of the metals it was determined that the values of As-Sb-W, were incremented since the inferior Cretaceous to the Neogene, the Ni-Pb-Zn-Sn were higher in the Cretaceous, decreasing in the Volcanic Paleogene-Neogene for increasing in the intrusive Neogene and Cd-Cr-Cu-Fe-Hg-Mo-V increased in the Paleogene-Neogene according to the inferior Cretaceous and decreasing in the Neogene. The analysis of correlation of Pearson and the Analysis of the Principal Components, determines five components:1) Zn-Cd-Pb- As-Cu-Sb-Sn-Fe 2) Ni-Mo-V-W-Fe 3) W-Fe, 4) Cr-Hg-Fe, 5) Hg Comparing with the established limits por the soils (Dutch Table) that surpasses the limits of intervention are arsenic, lead and zinc.